HUBUNGAN KONSTRUKSI SUMUR GALI DAN KANDUNGAN COLIFORM PADA AIR SUMUR TERHADAP KEJADIAN DIARE DI DESA UJUNG TERAN KECAMATAN SALAPIAN KABUPATEN LANGKAT TAHUN 2015 - Tumbur H. Simanullang; Meutia Nanda (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ABSTRACT               Dug wells are water sources which take benefit of ground’s water by digging a hole in the ground to get water. The indicator of water contamination by patghonic bacteria cause gastrointestinal disease such as diarrhea is coliform bacteria.               This type of research is an analytic cross sectional study design observationally to examine relations of risk factors that affect nutritional status, physical condition of well, coliform and utilization activities of dug well’s water with diarrhea. Population of 641 heads of households analyzed with Chi-square, Extact Fisher and multiple logistic regression.               Results of the study there was a relationship between nutritional status and diarrhea, there is a relationship between physical condition dug with Coliform content, there is a relationship between physical condition dug with diarrhea, there is no relationship between the content of Coliform with diarrhea , there is a relationship between the use of well water with diarrhea. Results of multiple logistic regression analysis found that diarrhea sigifikan affecting physical condition dug wells, and the use of well water.For health institutions is expected to increase the activity counseling on diarrhea prevention and hygiene – sanitation, especially related to the provision of clean water. For the community is expected to maintain cleanliness around the wells to prevent contamination of water wells. Keywords :      Coliform, Physical Condition Well Drilling, Well Water Utilization, Diarrhea.